José Luis Pardo’s notion of space and rethinking aesthetic’s subject (REVISTA NODO, 2022)
In this article we explore the notion of Space in José Luis Pardo’s aesthetics. With this purpose we depart from two of his main books where he explains this concept: Sobre los espacios. Pintar, escribir, pensar and Las formas de la exterioridad. In his work we understand the rethinking of aesthetics’ subject from beauty to sensibility. He answers of how we become sensitive beings by means of habit. His approach is non-subjective or pre-subjective, in terms of his attention to the world itself before subjectivity. The world becomes and expresses itself (even aesthetically). After this, we articulate the notion of space with Pardo’s conception of the city. The main thesis we propose is that the notion of space is crucial to think the redefinition of aesthetics’ subject, to no longer study beauty but to study sensitivity, departing from a non-anthropocentric perspective in order to explain how individuals become through habits, and afterwards they shape their own environment into an inhabitable territory.
Keywords: city; space; stethogram; image; time